From Industrialization to Innovation Justice: The Evolution of Indonesia’s Patent Law (1989–2024) and the Quest for a Post-TRIPS Legal Order - Raymond R. Tjandrawinata; Henry Soelistyo Budi; Ina Heliany (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: This study examines the evolution of Indonesia’s patent law through a philosophical, structural, and systemic lens, exploring why and how the national legal order has transformed from a state-controlled industrial tool to a plural innovation governance framework. It investigates six dimensions of legal evolution: the philosophical assumptions underlying each legislative phase; the structural redesign of the patent system; the historical and political causes driving reform; the normative implications for justice and inclusion; the epistemic method by which reform has been justified; and the prospective direction of post-TRIPS lawmaking.Objective: …Methods: Using a doctrinal-historical and hermeneutic approach, the analysis traces five major legislative stages: the industrial developmentalism of Law No. 6 of 1989; the liberal-international harmonization of Law No. 14 of 2001; the adaptive institutionalization of Law No. 13 of 2016; and the integrative, sustainability-oriented transformation of Law No. 65 of 2024. Each stage embodies a distinct worldview: from efficiency and control to equity and adaptability.Results: The study finds that Indonesia’s patent regime evolves dialectically rather than linearly—each reform emerging from contradictions between global market demands, constitutional values, and domestic innovation capacity.Conclusion: It concludes that the newest version marks a paradigmatic turn from TRIPS compliance to innovation justice. Yet it also introduces new paradoxes: digital complexity, regulatory overload, and unresolved distributive gaps. The paper proposes that future reforms should cultivate reflexive learning mechanisms within the legal system to sustain co-evolution with emerging technologies and social realities.